Sensor Networks for Monitoring Metro-de-Medellín System Infrastructure - Meneses, Gustavo (KnE Engineering, 2018)
Structural health monitoring systems rely on electronic instrumentation and telemetry for improving maintenance tasks, preventing catastrophic failures and following the behavior of critical variables for infrastructure works such as tunnels, highways, bridges and buildings. A proposal for the development of sensor networks for monitoring Metro-de-Medellín system infrastructure is presented. The adopted approach is based on the deployment of generic sensing units that can operate either individually or by constituting wireless personal area networks un-der the MiWi P2P protocol from Microchip. Different transceivers can be added to monitoring units that can act as gateways in order to allow collected data reach other networks, ranging from local area to metropolitan area coverage. Several sensors, digital and analog, can be attached to the generic units depending on the particular requirements of specific situations and monitoring locations. The results obtained from performed tests and the options considered for graphical user interfaces are also presented. Keywords: MiWi Protocol, Structural Health Monitoring, Short Data Service, Terrestrial Trunked Radio, Wireless Sensor Networks.